IT-Based YouTube Integration for Early Childhood English Vocabulary Learning: Teacher Perspectives - Ade Novia Maulana; Evi Selva Nirwana; Jhoni Warmansyah; Nur Rahma Hannia (Ta'dib, 2025)
English vocabulary acquisition forms the foundation for language development in early childhood. While Information Technology (IT) platforms like YouTube offer multimedia resources for language learning, research examining teacher perspectives on YouTube's role in vocabulary development remains limited. This phenomenological study explores how early childhood educators perceive and integrate YouTube for English vocabulary instruction. Twenty teachers from 18 institutions across three Indonesian provinces participated through interviews and documentation analysis. Data analysis employed open coding and axial coding to identify patterns and themes. Findings reveal two main themes: teachers recognize YouTube's effectiveness for vocabulary recognition and contextual usage, yet emphasize the need for structured implementation. Teachers perceive YouTube as effective when combined with three strategies: selecting age-appropriate content, providing active guidance during viewing, and implementing reinforcement activities such as storytelling and interactive games. This study contributes phenomenological insights into teacher experiences with IT-mediated language instruction and offers practical frameworks for integrating digital platforms into early childhood vocabulary development.